Study of new physiological characteristics as protein receptors (RP55) of light, color, heat, motion, smell, electric, vibration and position located in head, body and abdominal, found in mosquito larvae. - Vásquez Hidalgo, Antonio (Universidad de El Salvador.Facultad de Medicina, 2024)
The main objective of the research is to demonstrate new physiological characteristics receptors in the presence of mosquito larvae. 100 larvae of different species were collected and studied for a week in periods of 8-24 hrs. Larvae stages I, II, III and IV have photo-thermo receptors of light and heat housed in the body is divided into head, thorax and abdomen, perceive hot or cold environments, and have fibers in chest or hairs lining your body or abdomen, and a pair of antennae on the head. Stages II and III are more developed than the initial stages. They are attracted by the dark green at the bottom, a pair of eyes that perceive light and color. Have receptors proteins (RP55) that capture motion at a speed the slightest movement of waves in the water. Its nose is not well developed but have chemoreceptors. They adapt to changes in pH in alkaline media, are sensitive to chemical, thermal and mechanical changes nociceptors have electroreceptors or galvanoreceptores sensitive to electrical stimuli, have mechanoreceptors that are sensitive to touch, pain, pressure, gravity, sound. They have a GPS position that seems the guides. It is precisely in the fibers, mushrooms or bristles are recipients along with the micro villi in head, thorax and abdomen.